Principles of structural design : wood, steel, and concrete - Gupta, Ram S. (CRC Press, 2011)
Anyone involved with structural design, whether a student or a practicing engineer, must maintain a functional understanding of wood, steel, and concrete design principles. In covering all of these materials, Principles of Structural Design: Woo